ESTETIKA DAN MAKNA DESAIN RUPA PENANDA GAPURA DAN BANNER PENYAMPAI INFORMASI PENGELOLAAN DAN PENGOLAHAN SAMPAH (TPS) DI DUREN VILLA KOTA TANGERANG - Abidin Muhammad Noor; Desiana Nur Indra Kusumawati; Kusnadi; Andri Arthono (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
Abstrack Garbage is a problem in our life. So far, waste is considered a source of various diseases and pollutes air quality. So that not many people care about waste problems, especially on the display marking the Waste Management and Processing Place (TPS). Supporting the government's goal of making regulations on Household Waste Management which, among other things, states that everyone is obliged to reduce and manage waste. The Waste Management and Processing Based on Reduce Reuse Recycle (TPS3R) at Duren Villa is one of the TPS which is located at the front of the housing gate so that it has a marking on the entrance gate. Like a front yard gate that marks a residential area, the front of the building should be an artistic and iconic building and make the people who inhabit it proud. The methodology used is a qualitative analysis by taking data in search of new meanings from the entrance sign system of the trash can gate located at TPS 3R in Duren Villa and then using a meaning analysis method based on Levi Strauss' Structuralism theory. The result that will be obtained in the service is the design of the analysis of the meaning of a marking system at the gate of the 3R TPS area in Duren Villa. So it can be concluded that based on this, places that are not liked can be managed by giving an attractive sign on the initial appearance of entry in order to reduce the unfavorable impression of Duren Villa TPS. Keywords: Garbage, Duren Villa, Visual Desain,